Total synthesis of (–)-sacidumlignans B and D - Rout, Jeetendra Kumar; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The first total synthesis of naturally occurring sacidumlignans A (1), B (2), and D (4) was executed and the absolute configuration of 2 and 4 was determined. A diastereoselective α- methylation of a lactone was used as the key step for the control of the chiral centers of the central lignan core. An acid mediated dehydrative cyclization of an aldehyde to construct the dihydronaphthalene unit of 2 and the aromatization of the intermediate dihydronaphthalene derivative to synthesize 1 are the key reactions employed in this regard.

Synthesis of C-disaccharides through a one-pot alkynol cycloisomerization-reductive deoxygenation - Narute, Sachin B.; Rout, Jeetendra Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2013)
Keywords: C-disaccharides; carbohydrates; Epoxide-alkyne coupling; Gold catalysis; Reductive deoxygenation